2022
DOI: 10.3390/vaccines10071113
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of a Trivalent Inactivated Salmonella Vaccine Combined with the Live S. Gallinarum 9R Vaccine in Young Layers after Experimental Infections with S. Enteritidis, S. Typhimurium, and S. Infantis

Abstract: Worldwide, poultry infections by Salmonella are the cause of significant economic losses, not only due to reduced production (due to fowl typhoid disease), but also considering the efforts and control measures that must be constantly applied, especially due to zoonotic serovars. Poultry is a common reservoir of Salmonella and its transmission into the food chain is a risk for humans. The vaccination of layers plays an important role in the overall efforts to prevent Salmonella infections. An inactivated trival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…2). Our results were agreeing with the findings of previous studies (Deguchi et al 2009;El-Enbaawy et al 2013;Huberman et al 2022) which reported the efficacy of Salmonella inactivated vaccines to reduce the bacterial fecal shedding after challenged with the same serovars or serovars related to the same serogroups. It had been previously reported that vaccination of breeder chickens with inactivated vaccine reduced Salmonella prevalence and loads in their broiler progeny (Crouch et al 2020a).…”
Section: Discussionsupporting
confidence: 94%
“…2). Our results were agreeing with the findings of previous studies (Deguchi et al 2009;El-Enbaawy et al 2013;Huberman et al 2022) which reported the efficacy of Salmonella inactivated vaccines to reduce the bacterial fecal shedding after challenged with the same serovars or serovars related to the same serogroups. It had been previously reported that vaccination of breeder chickens with inactivated vaccine reduced Salmonella prevalence and loads in their broiler progeny (Crouch et al 2020a).…”
Section: Discussionsupporting
confidence: 94%
“…Likewise, Huberman et al (2022) developed an inactivated trivalent vaccine with an oil adjuvant, which was administered to day-old layers at 8 and 11 weeks of age. The study demonstrated effective protection against S. Infantis colonization [128].…”
Section: Vaccination As Prevention Tool Against S Infantis In Poultrymentioning
confidence: 78%
“…Despite the absence of robust cell-mediated immunity, killed vaccines are preferred over live vaccines due to biosecurity and safety reasons [198]. Additionally, multivalent inactivated vaccines are required to contain the spread of a wide range of Salmonella serovars present in poultry [199,200].…”
Section: Bacteriophagesmentioning
confidence: 99%
“…It has been shown that greater levels of IgA and IgY antibodies were produced in the bile and serum following the simultaneous use of live attenuated and killed Salmonella vaccines in broilers [201]. The combined use of both live and killed vaccination programs successfully reduced S. Typhimurium and S. Infantis colonization in young layers, providing broad protection [199]. 6.9.3.…”
Section: Bacteriophagesmentioning
confidence: 99%